Interventions for Promoting Meconium Passage in Very Preterm Infants-A Survey of Current Practice at Tertiary Neonatal Centers in Germany - Maximilian Gross; Helmut Hummler; Bianca Haase; Mirja Quante; Cornelia Wiechers; Christian F. Poets (MDPI AG, 2022)
Meconium passage is often delayed in preterm infants. Faster meconium passage appears to shorten the time to full enteral feeds, while severely delayed meconium passage may indicate meconium obstruction. Neonatologists often intervene to promote meconium passage, assuming that benefits outweigh potential risks such as necrotizing enterocolitis (NEC). We performed an anonymous online survey on different approaches to facilitate meconium passage among tertiary neonatal intensive care units (NICUs) in Germany between February 2022 and April 2022. We collected information on enteral nutrition, gastrointestinal complications, and interventions to promote meconium passage. We received 102 completed questionnaires (response rate 64.6%). All responders used interventions to promote meconium passage, including enemas (92.0%), orally applied contrast agents (61.8%), polyethylene glycol (PEG) (46.1%), acetylcysteine (19.6%), glycerin suppositories (11.0%), and maltodextrin (8.8%). There was substantial heterogeneity among NICUs regarding frequency, composition, and mode of administration. We found no differences in NEC incidence between users and nonusers of glycerin enemas, high or low osmolar contrast agents, or PEG. There is wide variability in interventions used to promote meconium passage in German NICUs, with little or no evidence for their efficacy and safety. Within this study design, we could not identify an increased risk of NEC with any intervention reported.